Electrochemical detection and photochemical detoxification of hexavalent chromium (Cr(vi)) by Ag doped TiO2 nanoparticles. Issue 8 (26th March 2015) - Ravishankar, T. N.; Muralikrishna, S.; Suresh kumar, K.; Nagaraju, G.; Ramakrishnappa, T.
Abstract : Schematic representation of electrochemical reduction and photochemical detoxification of Cr(vi ). Abstract : We are proposing a simple, green and one pot ionothermal protocol for the synthesis of Ag doped TiO2 nanoparticles. The prepared material was characterized by various spectroscopic techniques like P-XRD and XPS and then the electrocatalytic reduction and photocatalytic detoxification ability of the material towards Cr(vi ) were explored. Amperometric studies showed a linear range from 0.1 to 3.1 μM, and limits of detection and quantification of 0.01 μM and 0.033 μM, respectively. The material also showed better photochemical reduction of Cr(vi ) in sunlight compared to UV light. About 90% reduction of Cr(vi ) to Cr(iii ) was observed in 120 min in sunlight whereas 88% reduction was obtained in UV light in the same time. The Ag doped TiO2 nanoparticle modified glassy carbon has been used for electrochemical monitoring of Cr(vi ) in natural water samples.